Global Citizenship Perceptions of Students in Different Cultures - Çakmak, Zafer; Bulut, Birol; Taskiran, Cengiz (Common Ground Research Networks, 2016)
Currently it's possible to reach any knowledge fast and immediately with the technological developments of the modern world; new global economies are shaped with economical developments; each social system undergoes changes with social innovations to compose new social interactions, and new modes of communication. Civil insights aren't on the previous locations, anda re in a change and development process. Thus, a new concept, insight, and fields of citizenship flourishes which has been based on new forms of belonging, new rights, and responsibiltysets, and has started a proper sector related with discussing new alternate concepts like European Citizenship, Cultural Citizenship, Global Citizenship, Digital Citizenship. We've focussed in our study on the concept “Global Citizenship”, and the “Global Citizenship Perception Scale” which was developed by Clarisse Olivieri Lima [1] was used applied and examined. The study was conducted on 72 foreign students in Turkey attending several departments in Fırat University in 2014-spring semester to determine their “Global Citizenship Perceptions.” The distribution of findings based on gender, fluency in a foreign language, Internet use frequency and purpose were analyzed. In data analysis, t-test and ANOVA analysis were utilized in the study. Analysis of data was conducted using SPSS 17.0 program in the study. © 2016 International Journal of Learning and Teaching. All Rights Reserved.
Keywords: global citizenship; social studies